The Study of Laccase Activity as a Biosensor for Peatland Degradation in Oil Palm Plantations in Pesisir Selatan of West Sumatra: The Study of Laccase Activity as a Biosensor for Peatland Degradation in Oil Palm Plantations in Pesisir Selatan of West Sumatra - Harianti, Mimien; Budi Prasetyo, Teguh; Maira, Lusi; Junaidi, Junaidi; Herviyanti, Herviyanti; Anwar, Syaiful; Kasim, Susilawati (LPPM Universitas Andalas, 2023)
The aim of the research was to study enzyme activity as biosensors for peatland degradation in oil palm plantations. The study was conducted in Pesisir Selatan,West Sumatra, on two peatlands with different thicknesses and location coordinates, namely peat with a thickness of <3 m S: 02o18'45.5